2014
DOI: 10.1371/journal.pone.0094611
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S29 Regulates Metabolic Insecticide Resistance through Binding and Degradation of CYP6N3

Abstract: BackgroundMany diseases are transmitted by mosquitoes, including malaria, dengue fever, yellow fever, filariasis, and West Nile fever. Chemical control plays a major role in managing mosquito-borne diseases. However, excessive and continuous application of insecticides has caused the development of insecticide resistance in many species including mosquito, and this has become the major obstacle to controlling mosquito-borne diseases. Insecticide resistance is the result of complex polygenic inheritance, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Deltamethrin resistant mosquitoes demonstrated a 23-fold increase in the expression of the L39 gene (Tan et al, 2007), but this was not the case in the Bayvarol ® resistant mites studied here. Yu et al (2014) demonstrated that another ribosomal protein s29 regulates metabolic resistance by binding to CYP6N3, so perhaps the unbound versions of certain ribosomal proteins were more abundant during proteomic analysis of the sensitive mites.…”
Section: Discussionmentioning
confidence: 99%
“…Deltamethrin resistant mosquitoes demonstrated a 23-fold increase in the expression of the L39 gene (Tan et al, 2007), but this was not the case in the Bayvarol ® resistant mites studied here. Yu et al (2014) demonstrated that another ribosomal protein s29 regulates metabolic resistance by binding to CYP6N3, so perhaps the unbound versions of certain ribosomal proteins were more abundant during proteomic analysis of the sensitive mites.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, reinforced enzymatic detoxification is one of the most common methods of achieving insecticide resistance of insects . Enzymatic detoxification is identified as a metabolic resistance process that involves the biochemical transformation of insecticides and further increases the biodegradation of toxic insecticides . This generally occurs due to the continuously increased expression and/or induction and elevated activity of members of three detoxification enzyme families: cytochrome P450 proteins (CYPs), carboxylesterases (CarEs), and glutathione S‐transferases (GSTs) .…”
Section: Introductionmentioning
confidence: 99%
“…This generally occurs due to the continuously increased expression and/or induction and elevated activity of members of three detoxification enzyme families: cytochrome P450 proteins (CYPs), carboxylesterases (CarEs), and glutathione S‐transferases (GSTs) . It has been shown that CYPs are the primary enzyme family that is associated with resistance to chemical insecticides in insect species . To date, a total of 143 CYPs, which can be assigned to four clans (clan 4, clan 3, clan 2, and a mitochondrial clan), have been identified in T. castaneum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations